Words - the way they look like in time - Vivian Carla Calixto dos Santos (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
In this work a letter written more than a hundred years ago is focused and allows a study on aspects connected to language, in its articulation with time. For such purpose, the approach on the theme of authors as St Augustine, rescued by Paul Ricoeur, and Jorge Larrosa will be brought and let us think about language in its narrative dimension, that suggests, more than reveals, and enlarges senses not anchored in apparent borders. In this way, an approach with the story "The third margin of the river" is also proposed.